2016
DOI: 10.1080/14786419.2016.1244195
|View full text |Cite
|
Sign up to set email alerts
|

Two new prenylated flavonoids from the roots ofBerberis thunbergiiDC.

Abstract: Two new prenylated flavonoids, thunbergiols A (1) and B (2), along with three known compounds, chrysin (3), quercetin (4) and berberine (5) were obtained from the methanolic extract of roots of Berberis thunbergii DC. MS, NMR and other spectroscopic techniques were employed for their structural characterisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The medicinal properties of Berberis have been known and appreciated for thousands of years. Many of them are due to the presence of alkaloids with different pharmacological activities [2], being berberine one of the most active compounds [3]. Some species of Berberis contain predominant phenolic compounds in their leaves, such as chlorogenic acid and rutin [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The medicinal properties of Berberis have been known and appreciated for thousands of years. Many of them are due to the presence of alkaloids with different pharmacological activities [2], being berberine one of the most active compounds [3]. Some species of Berberis contain predominant phenolic compounds in their leaves, such as chlorogenic acid and rutin [4].…”
Section: Introductionmentioning
confidence: 99%
“…Berberis thunbergii DC., also known as Japanese barberry, is a dense, woody shrub with deciduous nature that can reach up to 2 m high and is often used as an ornamental plant due to the bright red tones of the leaves [10]. Native to Asia, it is also present in the USA and in several European countries [3,11]. B. thunbergii is also recognized as a healing plant in Asia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Traditionally, B. thunbergii is used in Iran, North America, China, and Japan, due to significant anticancer, anti-inflammatory, immunomodulatory, larvicidal, analgesic, nephroprotective, hepatoprotective, hypoglycemic, antidiabetic, antibacterial, antioxidant, antifungal, antiviral, and antiparasitic activities. [5][6][7][8][9] B. thunbergii is shown to have terpenoids, tannin, saponins, steroids, alkaloids, glycosides, carbohydrates, proteins, flavonoids, phenolic compounds, and essential oils as the major phytochemical groups. [7][8][9] The antioxidant compounds of B. thunbergii are glucaric acid, caffeoylglucaric acid, chlorogenic acid, luteolin-O-hexoside, quinic acid, dihydrokaempferol-O-hexoside, coumaroylquinic acid, methyl-caffeoyl-quinate, quercetin, rutin, quercetinhexoside, quercetin-O-acetylhexoside, 3,5-dicaffeoylquinic acid, quercetin-O-deoxyhexoside, and kaempferol-Odeoxyhexoside.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the above phytochemicals have a unique role in the therapeutic effects of this plant .9 However the ethnomedicinal plants have excellent remedial properties, several studies have indicated if they are combined with metallic nanomaterials such as silver, gold, iron, copper, titanium, zinc, manganese, cadmium, cobalt, and tin nanoparticles the medicinal effects will significantly increase. [6][7][8][9] Nanobiotechnology is a combination of nanotechnology and biotechnology and has a remarkable role in the development and application of many useful tools and technologies in life science-related research .10 In the past decade, nanobiotechnology has come to the fore as a science that has led to reform changes in medicines. Nanomaterials, which are the subject of our study, have unique competencies different from their macroscale counterparts due to their low volume/surface ratio and many advanced and new physiochemical properties such as color, solubility, strength, prevalence, toxicity, magnetic, optical, and thermodynamics .11 In recent years, biological methods that are nontoxic, cost-effective, and environmentally friendly have become the focus of interest compared to physicochemical nanoparticle synthesis methods .12 Various pathways have been developed for the biogenic or biological formulation of nanomaterials from the salts of different metal ions.…”
Section: Introductionmentioning
confidence: 99%